Travellers and influenza: risks and prevention - Goeijenbier, Marco; Wilder-Smith, Annelies (Journal of travel medicine, 2017)
Background: Influenza viruses are among the major causes of serious human respiratory tract infection worldwide. In line with the high disease burden attributab